Understanding co-production as a new public governance tool. Issue 3 (3rd July 2018) - Sorrentino, Maddalena; Sicilia, Mariafrancesca; Howlett, Michael
ABSTRACT: Co-production has become a buzzword for both scholars and practitioners in the past decade. This introduction to the thematic issue 'Co-production: Implementation problems, new technologies and new designs' unpacks the concept of co-production and illustrates how it has been operationalized on the ground in diverse country-specific contexts. To facilitate the analysis, we make a distinction between 'traditional' and 'non-traditional' forms of co-production, even though the practice has not really been around long enough to have established a tradition in the true sense of the word. However, these two distinct forms of co-production are highly useful conceptual lenses through which to view the finer details and nuances, to identify the enabling conditions and to foreshadow the governance challenges, but also to highlight the innovating role co-production plays in forging public services and public policies. Thanks to the rich and varied ways in which the contributors have approached this central topic; the thematic issue enables the research and practice to more fully appreciate the ins and outs of co-production and suggests the most promising directions for future study.